Revenue Sharing of Natural Resources in Africa : Reflections from a Review of International Practices - Brosio, Giorgio; Singh, Raju Jan (World Bank, Washington, DC, 2014)
The African continent is one of the world richest regions in oil, gas and minerals. Proven reserves have expanded and prospects improved recently making the continent an important player on the world stage. The share of natural resources in GDP is increasing rapidly. Exports of minerals and hydrocarbons account for more than a quarter of total exports in half of the sub-Saharan economies and the share of natural resources revenue (NRR) on total government revenue is expected to become dominant for an increasing number of countries. Wealth of natural resources offers opportunities but it also brings in challenges. Natural resources have generally been linked to a series of negative outcomes like economic decline, corruption and autocratic rule (McNeish, 2010). Oil and minerals reserves are often point source natural resources, being usually very spatially concentrated. Their discovery becomes almost inevitably a potential source of conflict between the governments, the people of the producing areas and those of the rest of the country (Fearon and Laitin, 2003). In other words, intergovernmental sharing is a big issue that needs a solution when natural resources are discovered and exploited. Full centralization of NNR is the exception rather than the rule, as we will observe in the paper. It is practiced for oil and gas by both autocratic regimes (such as Saudi Arabia and other Middle East countries), and fully fledged democratic systems, such as Norway and the UK. Full centralization does not imply, however, the absence of compensating mechanisms, or of indirect transfers in favor of the governments of the producing areas. In the UK, for example, Scotland receives no share of oil taxes, but is compensated with a larger share of block grants to local governments (the Barnett formula ). Norway rewards the local governments closer to the producing areas with generous infrastructure projects, such as tunnels and bridges linking very sparsely populated areas and islands. Autocratic countries may also use repression to quench the request for a share of NRR from their producing areas.